Wytrzymałość biegowa i pływacka studentów UKW Bydgoszcz = Speeding and swimming endurance of students UKW Bydgoszcz - Gwiździel, Diana; Cieślicka, Mirosława; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Gwiździel Diana, Cieślicka Mirosława, Zukow Walery. Wytrzymałość biegowa i pływacka studentów UKW Bydgoszcz = Speeding and swimming endurance of students UKW Bydgoszcz. Journal of Education, Health and Sport. 2016;6(8):489-503. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60941 http://ojs.ukw.edu.pl/index.php/johs/article/view/3782 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 19.08.2016. Wytrzymałość biegowa i pływacka studentów UKW Bydgoszcz Speeding and swimming endurance of students UKW Bydgoszcz Gwiździel Diana, Mirosława Cieślicka, Walery Zukow Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Do określenia poziomu wytrzymałości pływackiej i biegowej studentów kierunku Turystyka i Rekreacja Uniwersytetu Kazimierza Wielkiego w Bydgoszczy, wybrano metodę eksperymentu pedagogicznego, natomiast, jako technikę wybrano test, a narzędziem do przeprowadzenia badań został test Coopera. W odpowiedzi na główny problem badawczy, na podstawie przeprowadzonych badań można stwierdzić, że poziom wytrzymałości biegowej studentów Turystyki i Rekreacji plasuje się na poziomie dobrym i średnim, gdyż znaczna część grupy uzyskiwała takie wyniki. Natomiast w próbie pływackiej badana grupa wypadła znacznie gorzej, gdyż największa liczba uczestników uzyskała słaby wynik. Nieco mniej osób osiągnęło zadawalający rezultat. Zarówno w próbie biegowej, jak i pływackiej przedstawiciele płci męskiej uzyskiwali lepsze wyniki od przedstawicielek płci żeńskiej. Jednakże najbardziej widoczne różnice między obiema płciami można zaobserwować w próbie pływackiej, w której uczestniczki biegu w większej mierze wyniki słabe albo bardzo słabe, kiedy studenci przeważnie zadawalające. Słowa kluczowe: wytrzymałość, Test Coopera, pływanie. Abstract To determine the level of endurance swimming and cross-country students of Tourism and Recreation at the University of Bydgoszcz, you chose the method of pedagogical experiment, however, the technique chosen test, and a tool for testing was Cooper test. In response to the major research problem, on the basis of the study it can be concluded that the level of endurance cross-country students of Tourism and Recreation ranks of good and medium, since a significant part of the group it obtained such results. However, in an attempt to swim test group fared much worse, since the largest number of participants received a poor result. Slightly fewer people reached a satisfactory result. Both in an attempt to cross-country, swimming and representatives of the male experienced better outcomes than of the female sex. However, the most visible differences between the sexes can be observed in the test swim, in which participants run a greater extent the results of weak or very weak, when students usually satisfactory. Key words: endurance, Cooper Test, swimming.